EVALUASI RESPON SEISMIK STRUKTUR BANGUNAN UNIVERSITAS TERBUKA PALU TERHADAP GEMPA SULTENG 28 SEPTEMBER 2018 - Pinondang Simanjuntak; Sudarno P Tampubolon (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2022)
ABSTRACT The September 28th,2018 Central Sulawesi earthquake collapsed various buildings in Palu. One of the buildings that collapsed due to the earthquake was the structure of the Universitas Terbuka building Palu. Based on a survey to the building site, it can be seen that the collapse occurred in the dominance of melting in the column sections so that the structure was unable to stand upright. Therefore, to find out the main cause of the collapse of the Universitas Terbuka Palu building, it is necessary to analyze the seismic response of the structure. The method used is Spectra Response. Analysis of the calculation of deformation, storey drift and base shear is carried out to determine the stability and the main cause of the collapse of the building. The results showed that the Seismic Response of the Universitas Terbuka Palu building structure was not suitable for earthquake loads with the earthquake zoning of the Palu area determined based on SNI 03-1726-2012. The analysis shows that the deformation that occurs is greater than the allowable deformation and the field conditions indicate that the column is experiencing melting so that it collapses earlier than the beam. Keywords: seismic response spectra, Central Sulawesi earthquake, stability, deformation